MIGRASI SISTEM INFORMASI AKADEMIS UNTUK MENDAPATKAN TINGKAT INTEROPERABILITAS YANG LEBIH TINGGI - Sunarko, Budi (Jurnal Teknik Elektro, 2011)
The ordinary information systems had low interoperability, therefore they can only be operated through uniplatform, local access, single database, and single user. The invention of Internet and HTML hadlead some information system changes to be based on the web. Information system based on web have ahigher interoperability level, meaning that they can be operated through multiplatforms, remote access,multidatabases, and multiusers. The purpose of this research is to evolve some strategies and investigatesome components which are needed to conduct the migration of information system, from the ordinaryinformation systems to information systems based on the web. As a case study, migration strategies on anoperational ordinary information system with rigorous complexity are implemented. The migration of information system can be done through two strategies, with the same operatingsystem or different one. The only component that has to be migrated in the same operating system platformis the DBMS programs. On the other hand, the components that have to be migrated in the differentoperating system platform are the components of database and the DBMS programs. The database migrationcan be done by converting the database tables and move the data to the new database tables, whereas theDBMS migration can be done by rearranging the DBMS programs into the web aplication form by using CGIand HTML. In order to interact with the database, the suitable database drivers or ODBC have to be used. The conclusion of this research are : (1) web needs CGI and database drivers to interact with thedatabase, (2) the migration of the database from xBase to mSQL database tables can be done by usingdbf2msql, (3) the suitable information to be accessed through the web are those that are always available tobe accessed through remote multiusers, (4) the most important web aplication contains passwords, and (5)the information systems based on the web support the client/server system.